On-deck vs. laboratory analyses of the sound velocity of sediments from the Huanghai and Bohai seas - Baohua Liu; Jiewen Zheng; Jingqiang Wang; Lei Sun; Xiaolei Liu (Frontiers in Marine Science, 2024)
One popular method of obtaining the acoustic parameters of seabed sediments is by measuring the sound velocity of sediment samples in a laboratory. However, the effects of environmental variation and physical perturbation on acoustic properties are typically neglected in the application of such measured acoustic parameters. In this study, sediment samples were collected from the Huanghai and Bohai seas to measure sound velocity both on the deck and in the laboratory using a digital sonic measuring system. Additionally, sediment compositions, physical and mechanical properties and microstructures were determined. Sound velocity comparisons between on-deck and laboratory measurements indicate that laboratory-measured velocities are generally higher than those measured on the deck, with differences ranging from 1.45 m/s to 130.05 m/s, due to the water loss and densification of sedimentary particles in laboratory settings. The discrepancy of sound velocities measured in the laboratory and on the deck also differ based on the types of sediments sampled. Overall, the discrepancy increases with measurement frequency, increasing average grain diameter and sand content, as well as with decreasing clay content.